Estratégias para conservação e clonagem in vitro de mangabeira - Santana, Fernanda Vieira (2023)
Hancornia speciosa Gomes is a fruit tree, found in several regions of Brazil, but particularly important in the Northeast region. Due to the wide range of uses of its fruits, this tree species represents a source of income of families that extract the fruits from the natural populations. The genetic resources of mangabeira are mostly conserved by means of field collections, mainly due to the recalcitrant physiology of the seeds. Therefore, cryopreservation techniques and somatic embryogenesis are additionally explored, as alternatives to the conservation of the existing genetic variability and for the vegetative multiplication of promising genotypes. The objectives of this study were to: I – evaluate the efficiency of the droplet vitrification technique for long-term conservation of five mangabeira accessions (Água Boa; Japaratinga; Paratibe; Oiteiro; Terra Caída), and check if these accessions have any level of susceptibility to possible effects of cryopreservation; II – study maturation induction of somatic embryos from nodal and foliar explants of accession Terra Caída (TC) of the Germplasm Bank of Mangaba (BAGMangaba). For cryopreservation, shoot apices were subjected to different periods of exposure (30 and 50 min for test I; 25, 50 and 75 min for test II) to vitrification solution 2 (PVS2), prior to immersion in liquid nitrogen. To evaluate the effects of cryoprotective solutions and exposure times on shoot apices exposed or not to liquid nitrogen, regeneration percentages were recorded after 30 and 60 days of in vitro cultivation. For callus induction, leaf and nodal segments of the TC accession were cultivated in media with different putrescine concentrations (0, 250, 500, 750 and 1000 µM) in MS medium (Murashige & Skoog, 1962). After 120 days, the explants were transferred to a MS multiplication medium supplemented with 10 mg/L 2,4-D, 5mg/L benzylaminopurine (BAP), 1 g/L activated charcoal and 30 g/L sucrose and gelled with 3 g/ L Phytagel®. After 90 days in multiplication medium, embryogenic calli were identified and selected for the maturation phase of somatic embryos under water stress induced with polyethylene glycol (PEG, at 0 and 2%) and enriched with BAP (10 and 15mg/L). After 60 days, pro-embryos and maturing embryos were observed. The experimental results were analyzed by non-parametric tests using R software. It was possible to cryopreserve the studied accessions by droplet vitrification. Putrescine did not favor the development of embryogenic calli, and the presence of 2,4-D and BAP promoted differentiation into embryogenic calli. Nodal segments in combinations of 10 or 15 mg/L BAP with 2% PEG intensified the formation of pro-embryos and maturing embryos of the TC accession. The performance pattern of accessions from BAGMangaba could be evaluated by the cryopreservation technique. In addition, the concentrations of growth regulators and best types of explants for establishing a somatic embryogenesis protocol for mangabeira could be defined.